Kicking ASSessment: Using Information Fluency Assessment to Expand Librarian Roles, Engage in High-Impact Practices, and Create Sustained Contact with Online Learners. Issue 1 (2nd January 2017) - Adams, Katherine; Wiley, Paula
ABSTRACT: Iowa Wesleyan University (IW) has historically struggled with both assessment and supporting online students. Newly-appointed librarians and an impending re-accreditation visit prompted an increase in involvement and presence with assessment. In an attempt to expand the library's influence on campus, librarians took on a nontraditional role in the institutional implementation of LiveText, an assessment software. Librarians at IW have played an active and integral role in not only the initial roll-out of this software, but also in training and continuing support for students and faculty. Because of its importance to institutional learning outcomes, information fluency (IF) is being recognized as a high-impact practice across disciplines, and based on the results of this case study, librarians will pursue the creation of a required online IF course for online learners.